STUDIES ON PERSISTENT INFECTIONS OF TISSUE CULTURES : V. THE INITIAL STAGES OF INFECTION OF L(MCN) CELLS BY NEWCASTLE DISEASE VIRUS - Rodriguez, José E. (The Rockefeller University Press, 1964)
The initial stages of infection of L(MCN) cell populations with standard Newcastle disease virus (NDV(ST)) were analyzed in an effort to elucidate the steps leading to survival of the cultures and to the indefinite persistence of the infectious process at a low level. Cells were exposed in suspension to NDV at varying multiplicities and the monolayer cultures derived from such cells assayed at intervals for cellular growth rates, percentage of infected cells as determined by immunofluorescence, yields of viral progeny and of interferon, and, on occasion, resistance to superinfection with vesicular stomatitis virus. The percentage of cells calculated to be initially infected on the basis of adsorption data was found to match closely the percentage of immunofluorescent cells resulting from the first infectious cycle (up to 24 hours). Cells initially infected with NDV(ST) produced a mixed progeny of infectious virus (from 15 to 40 pfu/cell) and about 10 times as many non-infectious particles in 24 hours [NDV(L(MCN))], but little or no interferon. If all cells were infected the cultures ultimately died. At multiplicities of infection (m) of 2 or less the cultures survived with increasing ease as the percentage of infected cells was reduced. The number of pfu per infected cell was of the above order during the first 3 days; it declined thereafter. Limited secondary spread of the infection was noted by 48 hours and no further cycling was noted thereafter. As m decreased from 2.0 to 0.1 there was an increase in the yields of interferon and the time at which peak titers were reached. Addition of anti-NDV serum 2 hours after infection prevented measurable production of interferon. In contrast, following exposure of cells to NDV(L(MCN)) at multiplicities ranging from 20.0 to 0.2 (based on infectious virus) all cultures survived, no secondary spread was noted, the number of pfu per infected cells was reduced at the higher multiplicities, and the yields of interferon were similar and maximal by 24 hours and not affected by anti-NDV serum added after an adsorption period of 2 hours. It is concluded that the non-infectious virus particles in the progeny released from NDV(ST)-infected cells induce resistance in remaining cells or, if adsorbed simultaneously with infectious virus, abort the intracellular infectious process. In both instances interferon is produced which may then render additional cells resistant. The non-infectious component is considered an incomplete or defective product of viral replication and not merely thermally inactivated virus. NDV(ST) partially or completely inactivated at 37°C induced neither cellular resistance nor synthesis of interferon. The incomplete viral component behaved in all respects like ultraviolet-inactivated NDV(ST) except that it was significantly more efficient in inducing interferon synthesis. On the basis of the presented data a scheme has been devised and discussed which appears to explain satisfactorily the events which take place on initial infection of L(MCN) cells with NDV and which lead to the persistence of the infectious process.